Mild dyspnea presenting as 'crazy-paving' on chest computed tomography - M Oudah; D Slack (Greater Baltimore Medical Center, 2021)
Pulmonary alveolar proteinoisis (PAP) is a rare disease characterized by accumulation of proteinaceous material in the alveolar spaces. Here, we report a case of mild dyspnea with incidental 'crazy-paving' pattern on chest computed tomography (CT). Further evaluation and bronchoscopy found to have PAP.